Explored Publication Pattern of the Top Twenty Nirf-2020 Ranked Indian Institutions: an Evaluative Study - Chakraborty K.; Upadhyay N.; Upadhyay S.R. (My University, 2025)
Institutions ranking are getting more attention nowadays, as it shows institutions' status globally and influences students' decisions in selecting Institutions for admissions. Open access publications in scholarly research communication are important, but its significance in institutions' ranking is yet to explore. In this study, the authors tried to demonstrate and compare open access and commercial publication documents of the top twenty institutions (overall category) as per the National Institutional Ranking Framework (NIRF) 2020 report. According to NIRF-2020, maintaining their last year's positions, IIT Madras and IISc Bangalore bagged the first two ranks, followed by IIT Delhi on the third position among educational institutions with the score of 85.31, 84.18, and 81.33, respectively.In the study, it came out that in comparison to commercial publications open access publication perform better on the parameters of international collaboration, industry collaboration, the article in Q1 journals, citation impact, category normalized Citation Impact and Percentage of the document cited. Having the opinion that ranking provides an effective way of inspiring universities to continue, and hopefully increase, their commitment to open scholarship, this paper propose a parameter for open access publication to evaluate the ranking.This study may help ranking agencies evaluate approaches or a new policy for parameters weighted and researchers interested in research in this field. © 2021. All Rights Reserved